Integrated thematic instruction in the environment of Czech primary schools: A cross-sectional study - Barancová Klára; Fasnerová Martina; Balušková Kateřina; Kantor Jiří (Journal of Language and Cultural Education)
Integrated Thematic Instruction (ITI) (now also Highly Effective Teaching) is a type of teaching based primarily on one long-term unifying theme and its subsequent elaboration into branching themes and skills. Although the basic principles of ITI are reflected in the concept of the Czech curriculum, specifically in its project form (the Framework Educational Programme for Primary Education), there is only sporadic information on how ITI is used in pedagogical practice. The aim of this national cross-sectional study with a questionnaire was to determine the awareness of first-grade primary school teachers about the ITI model and to further focus on and explore selected applications of ITI in pedagogical practice. Only 23% of the teachers surveyed use the ITI model, and a higher level of awareness correlates with more frequent use. Teachers often use ITI in their practice in the form of one-day or weekly topics, and natural sciences are the most represented teaching areas. In most cases, teachers create their own materials for the ITI application. Still, they would welcome new ones (even though in 43% of cases, they consider the number of materials sufficient).